Astronomy in Science and in Human Culture Jawaharlal Nehru Memorial Lecture 1969 - Chandrasekhar, S. (SCHOOL SCIENCE, 2013)
It is hardly necessary for me to say how deeply sensitive, I am to the honour of giving this second lecture in this series founded in the memory of the most illustrious name of independent modern India. As Pandit Jawarharlal Nehru has written, “The roots of an Indian grow deep into the ancient soil; and though the future beckons, the past holds back.” I hope I will be forgiven if I stray for a moment from the announced topic of my lecture to recall, how forty-one years ago, I was one of thousands of students who went to greet young Jawaharlal (as we used to call him at that time) on his arrival to address the National Congress meeting in Madras that year. I recall also how the dominant feeling in all of us at that time was one of intense pride in the men amongst us and in what they inspired in us. Lokamanya Tilak, Mahatma Gandhi, Lala Lajpat Rai, Motilal Nehru, Jawaharlal Nehru, Sardar Patel, Sarojini Naidu, Rabindranath Tagore, Srinivasa Ramanujan—names that herald the giants that lived amongst us in that pre-dawn era.